Molecular cloning, characterization and expression analysis of complement components in red sea bream (Pagrus major) after Edwardsiella tarda and red sea bream Iridovirus (RSIV) challenge. Issue 82 (November 2018) - Noman Reza, Mohammad Ali; Mohapatra, Sipra; Shimizu, Sonoko; Kitamura, Shin-Ichi; Harakawa, Shogo; Kawakami, Hidemasa; Nakayama, Kei; Sawayama, Eitaro; Matsubara, Takahiro; Ohta, Kohei; Chakraborty, Tapas
Abstract: The complement system plays an important role in immune regulation and acts as the first line of defense against any pathogenic attack. To comprehend the red sea bream ( Pagrus major ) immune response, three complement genes, namely, pmC1r, pmMASP and pmC3, belonging to the classical, lectin and alternative complement cascade, respectively, were identified and characterized. pmC1r, pmMASP, and pmC3 were comprised of 2535, 3352, and 5735 base mRNA which encodes 732, 1029 and 1677 aa putative proteins, respectively. Phylogenetically, all the three studied genes clustered with their corresponding homologous clade. Tissue distribution and cellular localization data demonstrated a very high prevalence of all the three genes in the liver. Both bacterial and viral infection resulted in significant transcriptional alterations in all three genes in the liver with respect to their vehicle control counterparts. Specifically, bacterial challenge affected the pmMASP and pmC3 expression, while the viral infection resulted in pmC1r and pmC3 mRNA activation. Altogether, our data demonstrate the ability of pmC1r, pmMASP and pmC3 in bringing about an immune response against any pathogenic encroachment, and thus activating, not only one, but all the three complement pathways, in red sea bream. Highlights: Complement C1r, MASP and C3 genes from Pagrus major were isolated and characterized. All three genes showed the highest expression level in liver. Wave-like expression pattern of C1r, MASP and C3 was noticed after E. tarda exposure. RSIV infection resulted in transcriptional undulation in the three studied genes.